Synthesis and properties of a new AIE macrocyclic emitter with triarylamine backbone. Issue 36 (6th September 2017) - Itoi, Hiroaki; Jang, Taehee; Kanehashi, Shinji; Shimomura, Takeshi; Ogino, Kenji
Graphical abstract: Highlights: A new macrocyclic AIE emitter composed of triarylamine backbone was synthesized. The optical and electrochemical properties of the compound have been investigated. The compound shows dual emission both 423 nm and 505 nm. The compound exhibits enough thermal stability and high glass transition temperature. Abstract: A new macrocyclic AIE emitter composed of triarylamine backbone was successfully synthesized through convenient homocoupling procedure and easily purified by silica gel column chromatography, and recrystallization. The optical and electrochemical properties of the compound have been investigated. Intriguingly, the compound shows dual emission both 423 nm and 505 nm. This result implied that the violet emission was originated from an isolated component of the emitter, whereas the yellowish-green emission simultaneously exhibited AIE nature. The compound exhibits enough thermal stability and high glass transition temperature to be applied for organic devices.